Topical Application Using Non-ionic Surfactant for Formulation and Evaluation of Flavonoid Proniosomes - Venkateswarlu, Bendi Sri; Balasubramani, Ragul; Chandira, Rajappa Margret; Pethappachetty, Palanisamy (Asian Journal of Biological and Life Sciences)
It is the goal of this research to examine the topical use of non-ionic surfactant for the Formulation and Evaluation of Flavonoid Proniosomes developed for the transdermal delivery of Rutin. The Proniosomal topical gel was prepared using the slurry technique involved with a non-ionic surfactant, Maltodextrin, Cholestrol and Glycerin. A robust design of experiments was used to optimize the various formulation variables. The optimized PG4 formulation was evaluated for entrapment efficiency, SEM, ATR –FTIR, Viscosity, Spreadability, Drug content, in-vitro diffusion study, and stability studies. PG4 formulation showed the highest entrapment efficiency and the higher percent of drug content. Evaluated for viscosity and spreadability which indicated the ratio of span 80: cholesterol demonstrated presenting some fluctuation. The SEM exhibited spherical vesicles and the optimal particle size for proniosome. In vitro drug release was better drug release throughout the process. After 3 months of storage at refrigerator temperatures, the stability in the presence of the percentage drug content of Rutin proniosomal gel formulation 4. There are several benefits to using Span 80 as the nonionic surfactant in these Proniosomal gel formulations, including increased drug accumulation in the different skin layers and increased carrier potential for the topical administration of rutin for the treatment of rheumatoid arthritis.
Keywords: Cholestrol; Glycerin Drug content; In-vitro diffusion study; Maltodextrin; Proniosome